S12 Human rhinovirus impairs the innate immune response to bacteria in macrophages in chronic obstructive pulmonary disease. (December 2018) - Finney, LJ; Belchamber, KBR; Kemp, SV; Fenwick, P; Mallia, P; Donaldson, G; Johnston, SL; Donnelly, L; Wedzicha, JA
Abstract : Rationale: Human rhinovirus (HRV) is a common trigger of COPD exacerbations. Secondary bacterial infection is associated with more severe symptoms, greater airway inflammation and delayed recovery. Alveolar macrophages clear bacteria from the lung by the process of phagocytosis and maintain lung homeostasis through cytokine secretion. These processes known to be defective in COPD. The effect of HRV on alveolar macrophage function is unknown. Objectives: To investigate the effect of HRV on phagocytosis of bacteria and cytokine response by alveolar macrophages and monocyte derived macrophages (MDM) in COPD and healthy controls. Methods: Alveolar macrophages were obtained by bronchoscopy and MDM obtained by adherence. Macrophages were exposed to HRV 16 (multiplicity of infection 5), the TLR3 agonist polyI:C 30 µg/ml, interferon (IFN)-β 10 µg/ml, IFN-γ 10 µg/ml or media control for 24 hours. Phagocytosis of fluorescently-labelled Haemophilus influenzae or Streptococcus pneumoniae was assessed by fluorimetry. CXCL8, TNF and IL-10 release was measured using ELISA. Main results: HRV significantly impaired phagocytosis of H. influenzae by 23% in MDM (n=37) and 18% in alveolar macrophages (n=20) in COPD without impairing cell viability. HRV also significantly reduced phagocytosis of S. pneumoniae by 33% in COPD MDM. However, HRV had no significant effect on phagocytosis of bacteria in macrophages from healthy controls. Phagocytosis of H. influenzae was also significantly reduced by polyI:C but not by IFN-β or IFN-γ. HRV significantly impaired CXCL8, TNF and IL-10 responses to H. influenzae . The IL-10 response to H. influenzae was also significantly impaired by polyI:C, IFN-β and IFN-γ. Conclusions: HRV impairs phagocytosis of bacteria in COPD which could lead to an outgrowth of bacteria during COPD exacerbations. HRV also impairs cytokine responses to bacteria via the TLR3/IFN pathway which may prevent resolution of inflammation leading to prolonged exacerbations in COPD.